Engineered action at a distance: Blood-meal-inducible paralysis in Aedes aegypti. - Roya Elaine Haghighat-Khah; Tim Harvey-Samuel; Sanjay Basu; Oliver StJohn; Sarah Scaife; Sebald Verkuijl; Erica Lovett; Luke Alphey (Public Library of Science (PLoS), 2019)
BACKGROUND:Population suppression through mass-release of Aedes aegypti males carrying dominant-lethal transgenes has been demonstrated in the field. Where population dynamics show negative density-dependence, suppression can be enhanced if lethality occurs after the density-dependent (i.e. larval) stage. Existing molecular tools have limited current examples of such Genetic Pest Management (GPM) systems to achieving this through engineering 'cell-autonomous effectors' i.e. where the expressed deleterious protein is restricted to the cells in which it is expressed-usually under the control of the regulatory elements (e.g. promoter regions) used to build the system. This limits the flexibility of these technologies as regulatory regions with useful spatial, temporal or sex-specific expression patterns may only be employed if the cells they direct expression in are simultaneously sensitive to existing effectors, and also precludes the targeting of extracellular regions such as cell-surface receptors. Expanding the toolset to 'non-cell autonomous' effectors would significantly reduce these limitations. METHODOLOGY/PRINCIPAL FINDINGS:We sought to engineer female-specific, late-acting lethality through employing the Ae. aegypti VitellogeninA1 promoter to drive blood-meal-inducible, fat-body specific expression of tTAV. Initial attempts using pro-apoptotic effectors gave no evident phenotype, potentially due to the lower sensitivity of terminally-differentiated fat-body cells to programmed-death signals. Subsequently, we dissociated the temporal and spatial expression of this system by engineering a novel synthetic effector (Scorpion neurotoxin-TetO-gp67.AaHIT) designed to be secreted out of the tissue in which it was expressed (fat-body) and then affect cells elsewhere (neuro-muscular junctions). This resulted in a striking, temporary-paralysis phenotype after blood-feeding. CONCLUSIONS/SIGNIFICANCE:These results are significant in demonstrating for the first time an engineered 'action at a distance' phenotype in a non-model pest insect. The potential to dissociate temporal and spatial expression patterns of useful endogenous regulatory elements will extend to a variety of other pest insects and effectors.